2006
DOI: 10.1523/jneurosci.0453-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with an Estrogen Receptor   Ligand Is Neuroprotective in Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis is an inflammatory, neurodegenerative disease for which experimental autoimmune encephalomyelitis (EAE) is a model. Treatments with estrogens have been shown to decrease the severity of EAE through anti-inflammatory mechanisms. Here we investigated whether treatment with an estrogen receptor ␣ (ER␣) ligand could recapitulate the estrogen-mediated protection in clinical EAE. We then went on to examine both anti-inflammatory and neuroprotective mechanisms. EAE was induced in wild-type, ER␣-, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 102 publications
7
133
0
1
Order By: Relevance
“…Morales et al [170] demonstrated that treatment with an ERa ligand is sufficient to recapitulate the estrogen-mediated protection in EAE, consistent with a report by Elloso et al [69] that demonstrated that treatment with an ERa, but not an ERb, ligand could reduce acute EAE disease severity. The degree of preservation of neuronal integrity in the gray matter of estradiol and ERa ligand-treated mice with EAE in this study was striking, and this has major implications for neurodegenerative changes that occur ''beyond the lesion" in EAE and possibly MS.…”
Section: Estrogens and Multiple Sclerosissupporting
confidence: 59%
See 1 more Smart Citation
“…Morales et al [170] demonstrated that treatment with an ERa ligand is sufficient to recapitulate the estrogen-mediated protection in EAE, consistent with a report by Elloso et al [69] that demonstrated that treatment with an ERa, but not an ERb, ligand could reduce acute EAE disease severity. The degree of preservation of neuronal integrity in the gray matter of estradiol and ERa ligand-treated mice with EAE in this study was striking, and this has major implications for neurodegenerative changes that occur ''beyond the lesion" in EAE and possibly MS.…”
Section: Estrogens and Multiple Sclerosissupporting
confidence: 59%
“…The ERa selective ligand propyl pyrazole triol (PPT) provides neuroprotection and anti-inflammatory activities in brain in experimental models of neurodegenerative diseases, including ischemia [165], MPTP-induced neurotoxicity [52] and EAE ( [69,170]). The in vitro activity of PPT has been studied in neuronal cells [266], while our preliminary data demonstrate a direct anti-inflammatory activity of this ligand in microglia (unpublished results).…”
Section: Selective Er Modulatorsmentioning
confidence: 99%
“…Furthermore, the presence of mER in myelin (Arvanitis et al, 2004), which is a membranous product of the OL and lacks nuclei, indicates that estrogen may also play a role in myelin function. Animals pretreated with estradiol or PPT before immunization to induce EAE were protected from clinical signs of the disease via an ERa effect (Morales et al, 2006). Treatment with ERb ligands induced clinical protection later in disease (Tiwari-Woodruff et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…After puberty, MS occurs two times more frequently in the female than the male (Czlonkowska et al, 2005;Hughes, 2004), but pregnancy has a protective effect (Confavreux et al, 1998). Treatment of MS in humans and experimental allergic encephalomyelitis (EAE) in mice by estrogens ameliorates these diseases (Bebo et al, 2001;Morales et al, 2006;Soldan et al, 2003). An immunomodulatory effect had been suspected (Lang, 2004), but it has recently been shown that in EAE, estradiol exerts its ameliorating effect via ERa receptors in CNS-resident cells, not in lymphocytes (Garidou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the ER signaling pathway plays an important role in multi-tissue development. (49)(50)(51)(52) Therefore, we propose that LRP16, a coactivator of ERa, may display an important function in the carcinogenesis and progression of breast cancer. Besides, with ER, PR and Ki-67 (all P < 0.05) we also found that LRP16 expression was correlated with FHIT expression (P = 0.015) and CD133 expression (P = 0.038), implying co-operation of those important gene markers in the mechanism of breast cancer.…”
Section: Discussionmentioning
confidence: 99%